Competency and Work Environment as Determinants of Medical Staff Performance: Evidence from a Public Hospital in a Developing Economy - Novianto, Oktin; Noor Sembiring (Greenation International Journal of Tourism and Management, 2025)
Purpose. This study examines the effects of employee competency and work environment on medical staff performance in a public hospital operating under high service pressure. Design/methodology/approach. A quantitative survey was conducted among medical staff at a public hospital in Indonesia. Data were collected from 77 respondents and analyzed using multiple regression analysis supported by reliability and validity testing. Findings. The results indicate that employee competency has a positive and significant effect on medical staff performance. The work environment also shows a significant positive effect on performance. Furthermore, competency and work environment jointly explain a substantial proportion of variance in medical staff performance. Practical implications. Hospital management should prioritize competency development and the creation of a supportive work environment to improve service quality and staff performance. Originality/value. This study contributes to organizational analysis literature by integrating competency and work environment perspectives in explaining medical staff performance within a public healthcare context in a developing economy.